The Religion Faith of the Kyrgyzs - Aidaraliev, Amantur (Technium Social Sciences Journal, 2021)
Kyrgyzstan is a multi-ethnic and multi-faith society. This study highlights the role of religion in the development of Kyrgyz society in the XXth Century and the revival of it in the XXIst Century. In former USSR (Soviet Union) countries, these periods called “pre-Soviet era”, “Soviet-era” and “post-Soviet era”. The whole period during which the Kyrgyzs was exposed to Islam and adopted the faith divided into the following stages: i) from 9th to 14th centuries, ii) from 15th century to the second half of the 18th century, iii) from the end of the 18th century to the beginning of the 20th century, iv) from 1918 to 1991 (Soviet-era, atheism period), v) from 31 August 1991 (the date of the Independence Day and the collapse of the Soviet Era) to 2000, vi) from 2000 to present (Revival of Islam and other sects). The study discusses the development of islam in Kyrgyzstan at the above periods. Also, the development of post-Soviet democratic reforms in the Kyrgyz Republic has enabled the provision of many Islamic literatures, basic human rights, including the right to religious freedom. A democratic and open atmosphere in post-Soviet time had increased faith of true believers, however, is also attracted all kinds of non-traditional religious sects and groups. Thus, religion policy is used for various strategic and ideological dimensions and the role of religion in politics and in the life of society must be considered as one of the most important topic.